Structural Design and Strength Analysis of Lifting Machine for Home Appliance Flood Safety Tool: A Problem-based Learning - Sineri, Gabriel Ayrton Andares; Octary, Astrid Vanya; Ali, Muchammad Fachrizal; Iza, Nurlaely Rohmatul; Triawan, Farid (Indonesian Journal of Multidiciplinary Research, 2021)
In Indonesia, floods become an annual disaster, especially in the rainy season. The number of floods occurs in Indonesia in 2019 reached 1,277 cases. The floodwater can cause massive damage to the home appliance, especially when contacted with electronic devices. Moreover, the lifting machine comes as an excellent solution, securing the electronic device when floods come. A preliminary design of a hydraulic scissors lifter for elevating the home appliance during floods is introduced along with its static and fatigue strength analyses. The proposed design comes up with a combination of scissors lifter mechanism combined with the hydraulic jack device. The analyses in the critical components of the lifting machine - the support link and the scissors rod link - are presented. The lowest and upper conditions are assumed and resulted in a dynamic safety factor of 1.252 for the lowest position and 3.11 for the highest position. These values indicate that the proposed design offers excellent safety. Additionally, this work can be classified as teaching material for the machine element course.